A STUDY ON CUSTOMER SATISFACTION TOWARDS MASALA PRODUCTS IN SHRI KANNAN DEPARTMENTAL STORES, COIMBATORE (Journal of Pharmaceutical Negative Results, 2023)
“Aachi Masala” is the popular of Masala as the household among the millions of people today, it is doing Masala trading into the field of pure spice powders like Turmeric, Chilli, Coriander powders, and Matten, Chicken, Kulambu Masalas etc., this curiosity lets to enter into masala world with boldness. This masala encountered a lot of hurdles, since selling masala products during those days to the oriental women who are traditionally conservative. It is not easy to sell. It is concept sealing on “Easy Cooking” rather than marketing food products with self-determination and persistent attempts, it is able to get into the kitchens of our country and the rest of the world. The store may look like a wonder, but the hard work, the pot holes and the bumps on the way to producer. The person who stood behind produce masala for all those achievements was with help of their business partner. The main objective of this research is to identify the consumer satisfaction of Aachi masala products in Coimbatore District. The suggestion is help to improve the quality of the Product.